Cross-National Differences in Managers' Willingness to Justify Ethically Suspect Behaviors: A Test of Institutional Anomie Theory - Cullen, John B.; Parboteeah, K. Praveen; Hoegl, Martin (Academy of Management Journal, 2004)
With globalization, understanding unethical conduct from a cross-national perspective is becoming more important. We used institutional anomie theory to develop hypotheses relating four national culture variables (achievement, individualism, universalism, and pecuniary materialism) and social institutions (economy, polity, family, and education) to managers' willingness to justify behaviors generally considered ethically suspect. Data from 3,450 managers from 28 countries support our hypotheses for universalism, pecuniary materialism, economy, family, and education. Implications for future research and practice are discussed.